Analysis of the Effect of Learning Models, Cognitive Abilities, and Facilities on Students' Academic Achievements - Mohzana; Firman Aziz; Muhammad Ridhwan; Susatyo Adhi Pramono; Iwan Henri Kusnadi; Bayu Purbha Sakti (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study analyses the influence of learning models, cognitive abilities, and facilities on students' academic achievement. Improving student learning outcomes heavily depends on the learning model used in the teaching and learning process. Both internal and external factors influence academic achievement. Internal aspects include students' cognitive capacity, while external factors include the availability of facilities. Students' cognitive capacities contribute to their understanding and application of the concepts taught, and selecting an appropriate learning model can enhance the efficacy of the learning process. Conversely, a better learning environment is supported by sufficient facilities. This study used a quantitative methodology based on survey research. Questionnaires distributed in senior high schools were used to gather data. In particular, the study found that student's academic achievement improved when they were more actively involved in and understood the content through technology-based learning models that were interactive and centred around technology. Compared to pupils with lower cognitive abilities, those with higher cognitive abilities tend to do better in school. Comfortable classrooms, access to technology, and sufficient teaching materials are all examples of full and high-quality learning facilities that positively affect student learning results. Using multiple linear regression analysis, we find that all three factors, the learning model in particular, contribute significantly to students' performance in the classroom. These results show that to raise the bar for education, we must enhance learning strategies, help students hone their cognitive capacities, and build better classrooms.